Extraordinary Giant Basal Cell Carcinoma with Full-Thickness Infiltration of the Abdominal Wall: Single-Staged Resection and Simultaneous Reconstruction. Issue 2 (March 2014) - Pierer, Gerhard; Pülzl, Petra; Deluca, Jenny; Müller, Hansgeorg; Zelger, Bernhard; Putzer, Daniel; Eisendle, Klaus
Background: Basal cell carcinoma (BCC) is the most frequent form of invasive skin cancer. BCCs usually show a slow progression and rarely metastasize; however, around 1% achieve a "giant" size, larger than 5 cm in diameter. Rarely, BCCs larger than 20 cm are reported in the literature. Objective: We report a case of a giant BCC, measuring 25 × 13 × 5 cm, involving the abdominal wall. The article describes the curative surgical procedure, which resulted in an excellent aesthetic result.